Selected advanced themes in ethical hacking and penetration testing - Buthayna AlSharaa; Rawan Masadeh; Mohammad Alqaisi; Saed Thuneibat (Institute of Advanced Engineering and Science, 2023)
Since 1980 cyberattacks have been evolving with the rising numbers of internet users and the constant evolving of security systems, and since then security systems experts have been trying to fight these kinds of attacks. This paper has both ethical and scientific goals, ethically, to raise awareness on cyberattacks and provide people with the knowledge that allows them to use the world wide web with fewer worries knowing how to protect their information and their devices with what they can. Scientifically, this paper includes a deep understanding of types of hackers, attacks, and various ways to stay safe online. This research investigates how ethical hackers adapt to the current and upcoming cyber threats. The different approaches for some famous hacking types along with their results are shown. Python and Ruby are used for coding, which we run on Kali Linux operating system.